Let it bang : a young black man's reluctant odyssey into guns - Young, R. J., (Writer) (Houghton Mifflin Harcourt, 2018)
"A story of race, guns, and self-protection in America today, through the quest--funny and searing--of a young black man learning to shoot a handgun better than a white person"--